Divorce Cases Triggered By Online Infidelity (Emotional Affair) In Indonesian Law - Hendri Saputra; Akbarizan (JAWI : Journal of Ahkam Wa Iqtishad, 2026)
This research aims to analyze the phenomenon of divorce triggered by online infidelity (cyber infidelity) or emotional involvement (emotional affairs) within the framework of positive law and Islamic law in Indonesia. In the era of digital disruption, the paradigm of domestic betrayal has shifted from mere physical relations to cyber interactions that violate the principle of loyalty. The research method used is normative legal research with a qualitative approach through library research. The results indicate that although online infidelity often does not reach the stage of physical adultery (intercourse), judges tend to interpret it as a form of continuous dispute and disagreement as regulated in Article 116 letter (f) of the Compilation of Islamic Law (KHI) and Article 19 letter (f) of Government Regulation No. 9 of 1975. The validity of digital evidence, such as WhatsApp screenshots and social media activity, is recognized as legitimate legal evidence under the ITE Law, provided it is not obtained through illegal wiretapping. Regarding the legal implications, online infidelity can influence the determination of child custody (hadhanah) in the best interest of the child; however, it generally does not automatically alter the division of marital property unless there is proof of asset misappropriation for the sake of the affair. This research concludes that there is a need for more specific regulations regarding digital evidentiary procedures in family cases to maintain family resilience in the digital age.